Knowledge Co-Production between University Research Teams and High School Teachers: A comparative study about teachers’ and students’ narratives in Metropolitan Area of Buenos Aires and Medellin (Itinerarios Educativos, 2024)
This paper discusses the case of an international collaborative research carried out by two teams of university researchers and secondary school teachers, one in the Metropolitan Area of Buenos Aires, Argentina and the other in Medellín, Colombia. The objective of the research was: to reconstruct and analyze, through their narratives, the experiences that teachers and students develop around educative inclusion, peacebuilding and citizenship in high schools that serve young people in situation of socio-territorial segregation, in the Metropolitan Area of Buenos Aires and in Medellín.The university teams worked collaboratively with 4 schools, 2 from Argentina and 2 from Colombia. In each school, from 2 to 3 teachers joined the research group. They were trained to participate from the first phase of project formulation to the data analysis. The field work was carried out mainly through playful-creative and reflective workshops, on the one hand with teachers, on the other hand with students.The paper reflects on the problems and achievements experienced in the collaborative research process. It also presents some of the main results obtained in terms of knowledge production.
Keywords: Collaborative research – High School - Inclusion – Peace building